Numerical simulation of ignition delay time for petroleum and renewable fuels. (15th November 2021) - Lee, Hao; Dahiya, Anurag; Lin, Kuang C.; Chen, Xiang-Xin; Wang, Wei-Cheng
Highlights: The ignition delay times of petro- and renewable fuels were numerically simulated. HRJ has the shortest ignition delay time in the low temperature range. The ignition delay time of all fuels was shorter when increasing the pressure. Abstract: In this research, the composition and proportion of surrogates were first determined according to the composition of the petrochemical and renewable fuels. Then, the CHBR model in CHEMKIN-Pro software was used to verify the ignition delay time of HRJ, JP-5, and HRD. The differences in the ignition delay time of the fuels under an equivalence ratio of 1.0, different pressures (8, 11, 30 bar), and a pressure of 20 bar, and different equivalence ratios (0.5, 1.0, 1.5) are discussed. Among the three types of aviation fuel, the ignition delay time of HRJ in the low-temperature range was the shortest, while that of JP-5 was the longest. The average ignition delay time of HRJ in the low-temperature range under different equivalence ratios and pressures was approximately 59% and 57% lower than that of JP-5, respectively. On the other hand, the average ignition delay time of HRD in the low-temperature range at different equivalence ratios and pressures was 45% and 55% lower than that of petrochemical diesel, respectively. The ignition delay time of all of the fuels was shorter when the pressure was increased.